2016
DOI: 10.1097/tp.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rabbit Antithymocyte Globulin Dose on Long-term Outcomes in Heart Transplant Patients

Abstract: These retrospective data suggest that a cumulative rATG dose of 4.5 to 7.5 mg/kg may offer a better risk-benefit ratio than lower or higher doses, with acceptable rates of infection and posttransplant malignancy. Prospective trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Regarding malignancy, the rarity of events makes an accurate assessment of the impact of specific rATG doses difficult. In the retrospective study by Aliabadi et al, 40 in which patients were followed up for a median of 104 months, Kaplan-Meier estimates for freedom from malignancy did not differ between the 3 rATG dose groups (<4.5 mg/kg, 4.5-7.5 mg/kg, or >7.5 mg/kg) but the time to tumor development was significantly shorter in the high-dose cohort. A recent systematic review concluded that the risk of posttransplant lymphoproliferative disease (PTLD) is not influenced by rATG dose across all organ types or specifically in heart transplantation.…”
Section: Impact Of Ratg Dose On Safetymentioning
confidence: 86%
See 3 more Smart Citations
“…Regarding malignancy, the rarity of events makes an accurate assessment of the impact of specific rATG doses difficult. In the retrospective study by Aliabadi et al, 40 in which patients were followed up for a median of 104 months, Kaplan-Meier estimates for freedom from malignancy did not differ between the 3 rATG dose groups (<4.5 mg/kg, 4.5-7.5 mg/kg, or >7.5 mg/kg) but the time to tumor development was significantly shorter in the high-dose cohort. A recent systematic review concluded that the risk of posttransplant lymphoproliferative disease (PTLD) is not influenced by rATG dose across all organ types or specifically in heart transplantation.…”
Section: Impact Of Ratg Dose On Safetymentioning
confidence: 86%
“…A retrospective single-center analysis of 523 heart transplant patients by Aliabadi et al 40 analyzed infection rates in the subgroup of patients given a total rATG dose of less than 4.5 mg/kg, 4.5 to 7.5 mg/kg, or greater than 7.5 mg/kg. Kaplan-Meier estimates indicated the 10-year incidence of severe infection to be 37%, 23%, and 45%, respectively ( P < 0.001).…”
Section: Impact Of Ratg Dose On Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…There is tentative evidence, however, concerning the question of whether lower rATG dosing reduces the risk for PTLD. Aliabadi et al performed a retrospective single-center analysis in which outcomes in 523 HTx patients (including 19 patients aged 5–18 years) were assessed according to cumulative rATG dose (<4.5 mg/kg, 4.5–7.5 mg/kg, or >7.5 mg/kg) [ 63 ]. There were no cases of PTLD in patients given a total dose of up to 7.5 mg/kg.…”
Section: Safety Issuesmentioning
confidence: 99%